The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000353134
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Surgery-Associated Acute Kidney Injury

Abstract: Cardiac surgery-associated acute kidney injury (CSA-AKI) is a common and serious postoperative complication of cardiac surgery requiring cardiopulmonary bypass (CPB), and it is the second most common cause of AKI in the intensive care unit. Although the complication has been associated with the use of CPB, the etiology is likely multifactorial and related to intraoperative and early postoperative management including pharmacologic therapy. To date, very little evidence from randomized trials supporting specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
141
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(171 citation statements)
references
References 236 publications
6
141
1
13
Order By: Relevance
“…Notably, in spite of the pharmacological interventions for CSA-AKI including the use of natriuretic peptides and dopamine agonists, there has been no clearly defined medicine for the treatment of this disorder [3]. In particular, a multisite trial in Japan showed that atrial natriuretic peptide did not significantly improve renal function in cardiac surgery patients with AKI [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in spite of the pharmacological interventions for CSA-AKI including the use of natriuretic peptides and dopamine agonists, there has been no clearly defined medicine for the treatment of this disorder [3]. In particular, a multisite trial in Japan showed that atrial natriuretic peptide did not significantly improve renal function in cardiac surgery patients with AKI [36].…”
Section: Discussionmentioning
confidence: 99%
“…CSA-AKI is caused by multiple factors, which involve different injury pathways including metabolic abnormalities, ischemia and reperfusion injury, neurohormonal activation, inflammation, and oxidative stress [2]. Due to the differences in baseline characteristics and surgery types, studies of the epidemiology of CSA-AKI in recent years showed the range of CSA-AKI incidence is between 8.9 and 39% [3]. Renal impairment during cardiac surgery is often associated with renal hypoperfusion caused by the bleeding complications [4], while exposure of blood to the cardiopulmonary bypass (CPB) pump and circuit often activate different inflammatory pathways [5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, it can be stated that the preoperative and operative periods are important for AKI development, but the use of classical markers such as SCr levels to diagnose AKI can cause a delay in the diagnosis. To prevent CABG-related AKI, three predictive risk scores based on preoperative variables have been developed: the Cleveland Clinic Score, the Mehta Score and the Simplified Renal Index Score [7]. However, there has been no consensus among authors with regard to recommending the use of a specific score to predict AKI before CABG.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of chronic inflammatory processes, atherosclerosis might affect both coronary and renal arteries. In this context, coronary artery disease was found to be closely associated with AKI [7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation